Adult pilocytic astrocytomas: challenging the benign paradigm with surgical risks, recurrence dynamics, and molecular insights - Mitschang, Dorothea; Kleineidam, Helena; Hinz, Felix; Sahm, Felix; Unterberg, Andreas; Krieg, Sandro; Dao Trong, Huy Philip; Lenga, Pavlina (Neurosurgical review, 2025)
Purpose Adult pilocytic astrocytoma (APA) is rare and clinically distinct from pediatric counterparts. Despite generally favorable prognosis, recurrence rates vary significantly based on tumor characteristics and surgical approaches. Literature regarding the influence of tumor volume, location, and patient age on surgical outcomes and survival is limited and inconclusive. This study addresses these gaps, evaluating the combined impact of these variables on APA prognosis and management. Methods We retrospectively analyzed 32 adult patients with surgically treated APA at our institution (2014-2023), examining demographics, imaging, histology, and outcomes. Results Mean age was 35.8 years (SD 11.6); 59% were male. Median Karnofsky Performance Score (KPS) at admission was 90% (range 50-100%). Infratentorial tumors (56%) correlated significantly with lower KPS, increased cranial nerve deficits, cerebellar symptoms, hydrocephalus risk, prolonged operative time, higher CSF leaks (11%), and frequent revision surgeries. Gross total resection was achieved less frequently in infratentorial (33%) compared to supratentorial tumors (43%). Overall recurrence rate was 50%, strongly predicted by higher Ki-67 proliferation indices (p < 0.05), whereas resection extent alone lacked significant correlation. BRAF mutations occurred in only 38% of recurrent cases, highlighting APA’s distinct molecular profile. Five-year mortality was 6%, exclusively in High-Grade Astrocytoma with Piloid Features (HGAP). Conclusion Our findings challenge assumptions of benign clinical courses for APAs. Infratentorial tumors present increased surgical challenges and require tailored management. With recurrence rates of 50% and Ki-67 as a key prognostic marker, APA treatment demands personalized, biomarker-guided strategies beyond conventional surgical approaches.
Gesehen am 22.01.2026